Research of the Defect Model Based on Similarity and Association Rule - Wanjiang Han; Lixin Jiang; Xiaoyan Zhang; Tianbo Lu; Sun Yi; Li Yan; Weijian Li (Institute of Advanced Engineering and Science, 2014)
In order to detect defects efficiently and improve the quality of products, this paper puts forward the concept about defect classification model and defect association model by a lot of defect data. The technology of similarity is applied to defect classification model, and the idea of Knowledge Discovery in Database is applied to defect association model. Defect classification model can analyze the defect efficiently and provides the basis of solving problems quickly while defect association model can be used to detect early and prevent problem, which can make effective improvements to testing and development. This paper summed up GUI defect model based on a large number of interface defects. The model is useful to improve the accuracy of forecast and be used for test planning and implementation through the practice of several projects. DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.5452